Bodily self-representation and ‘Everyday resistance’ of Gao-Da-Zhuang women in China - Li,Yijin (2025)
RedNote (Xiaohongshu) is one of the most influential women-centered platforms in China. Due to its highly feminized features, female users curate and share contents related to their body image, reflecting the prevailing representations of Chinese aesthetic ideals and normative femininity. This thesis examines Gao-Da-Zhuang (tall, large-sized and strong/muscular) women’s bodily self-representation on RedNote, aiming to explore the complex interplay of power and resistance on women’s body and discourse of femininity in China. Building on Foucauldian feminists’ (such as Bordo) perspective of ‘body as a site of both power and resistance’, this thesis investigates how Gao-Da-Zhuang women, positioned among different discourses, subtly practice specific tactics against the hegemonic femininity of ‘Pale, young and slim’ and negotiate their feminine identity through the act of bodily self-representation on RedNote. In this study, multimodal critical discourse analysis was adopted to analyze the selected 30 posts that are produced by 6 Gao-Da-Zhuang women (as creators on RedNote), unpacking their specific practices of tactics and bodily self-representations. To construct their Gao-Da-Zhuang identity, they employ their bodies as tactical spaces, not ostensibly resisting against the system, while subtly subverting the hegemonic femininity through practicing multiple tactics. For example, referring to the tactic what de Certeau (1984) describes as ‘the stories of miracle’, Gao-Da-Zhuang women narrate transformative stories which reverse the power of relationship within the discourse of femininity. As in these stories, the dominant femininity of ‘Pale, young and slim’ is no longer socially recognizable but remains frustrating problem, being Gao-Da-Zhuang become the solution and relief. Thus, the Gao-Da-Zhuang ideology is positioned as a success of cultural subversion. Furthermore, this thesis also draws on the perspective of (post)feminism and healthism. The (post)feminism which foregrounds the self-choice and individuality is indeed a ‘pseudo-empowerment’ — ostensibly empowers women the autonomy to shape their bodies, while indeed uses the emphasis on ‘individual choice’ to obscure the gendered and structural inequalities (Ye & Krijnen, 2024). Under the healthism discourse, in the name of ‘health’, practices are socially acceptable, encouraged and even promoted. It appears that being bodily healthy has become a way of gaining recognition and satisfying social expectations. ‘Appearing healthy’ has become a tactic for Gao-Da-Zhuang women to construct their feminine identity.
Keywords: Gao-Da-Zhuang women; Bodily self-representation; Everyday resistance; RedNote; (Post)feminism; Healthism